2010
DOI: 10.1111/j.1600-079x.2010.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin induces neural SOD2 expression independent of the NF‐kappaB pathway and improves the mitochondrial population and function in old mice

Abstract: Aging is commonly defined as a physiological phenomenon associated with morphological and functional deleterious changes in which oxidative stress has a fundamental impact; therefore, readjusting the oxidative balance should have beneficial effects. In our study, we tested the antioxidant melatonin in old mouse brains and showed positive effects at the cellular and mitochondrial levels. Melatonin attenuated β-amyloid protein expression and α-synuclein deposits in the brain compared to aged group. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 58 publications
4
31
0
Order By: Relevance
“…These changes were prevented by melatonin administration in a concentration-dependent manner. Garcia-Macia et al (2011) reported that melatonin induces neural SOD2 (mitochondrial MnSOD) expression independent of the NF-κB pathway in the brain tissues of old mice which also implies Nrf2 induction by melatonin.…”
Section: Transcription Factor Nrf2: An Emerging Conceptmentioning
confidence: 97%
“…These changes were prevented by melatonin administration in a concentration-dependent manner. Garcia-Macia et al (2011) reported that melatonin induces neural SOD2 (mitochondrial MnSOD) expression independent of the NF-κB pathway in the brain tissues of old mice which also implies Nrf2 induction by melatonin.…”
Section: Transcription Factor Nrf2: An Emerging Conceptmentioning
confidence: 97%
“…The endogenous mitochondrial antioxidant enzyme manganese superoxide dismutase (MnSOD) is upregulated by treatments that improve insulin sensitivity (18,25,46) and may be playing a role in the regulation of insulin action. However, interventional studies are needed to explore this possibility.…”
mentioning
confidence: 99%
“…Numerous biological pathways and molecular mechanisms that appear to be involved in the bi-directional cross-talk. Further, given the immunomodulatory effects of ADs and CTs (Bondy et al 2010;Garcia-Macia et al 2011;Min et al 2011;Racagni et al 2011;Ramirez-Rodriguez et al 2011), their associated effects on circadian rhythms Hickie and Rogers 2011), we suggest that these therapeutic agents may exert some of their chronobiological effects via immune mediation. This paper has provided an overview of the biological pathways which may mediate the bidirectional cross-talk between the immune and circadian systems.…”
Section: Discussionmentioning
confidence: 98%
“…IL-1b, TNF-a) and oxidative stress in the striatum, cortex, HC and hypothalamus (Shen et al 2007;Tyagi et al 2010). Other studies have shown melatonin suppresses NF-jB production and reduces oxidative stress in the CNS (Bondy et al 2010;Garcia-Macia et al 2011). In the same LPS model of immune challenge, melatonin attenuated chemokine expression (i.e.…”
Section: Antidepressantsmentioning
confidence: 96%
See 1 more Smart Citation